A Critical study of the Methodology of Joseph Schacht in Hadith’s Research - Ahmad, Mehmood; Tayyab, Muhammad Mansha (Journal of Islamic and Religious Studies, 2017)
In general, the results of research studies conducted by Professor Joseph Schacht and his fellows on criticism of Ahadith are contradictory with the results of Muslim Scholars. Muslim Scholars, point of view is that Muhaddithin have opposed, with full power, the condemnable tries for fabrication of Ahadith. Valuable principles for the identification of authentic and unauthentic traditions were the result of the struggles done by Muhaddithin. With the help of these principles the categorization of Ahadith came in to practical. Professor Joseph Schacht argues that the material presented as Ahadith and Sunna of Prophet by Muslim scholars is the production of later times. According to his point of view, there is no authentic hadith in the bulk of traditions and if assumed that there are few authentic, they are also mixed up with unauthentic and there is no possibility of identification of authentic one. This study is a try to identify the mistakes of his research approach.